Genetic Algorithm-Based Optimization of Mass Customization Using Hyperledger Fabric Blockchain - Baygın, Nursena; Karaköse, Mehmet (My University, 2022)
With the developing technology, the production model, which is structured in line with user requests, has become a very popular topic. This production model, which expresses individualization, has become increasingly common. For this reason, it attracts the attention of many researchers and company executives. At this point, studies are concentrated on the concept of mass customization, which expresses personalized production. Considering the related studies, various difficulties are encountered in this production model on issues such as cooperation, trust, and optimization. In this proposed method, a blockchain-based platform is designed to solve the problems of cooperation and trust, one of the most important problems of mass customization. In addition, in this study, the problem of optimization of the production and supply chain process in the manufacturing sector has been examined. This process includes reaching from the producer to the consumer and many parameters. Therefore, the optimization of this process is a very difficult problem. A two-stage system has been proposed to find a solution to this problem. In the first stage, a reliable platform was created by bringing together service providers and buyers in the manufacturing sector with blockchain. In the second stage, the most suitable parties were selected by a genetic algorithm.
Keywords: Genetic Algorithm; Blockchain; Smart Contract; Mass Customization.